Simultaneous dissociation of CO2 and H2O to syngas in a surface-wave microwave discharge. (9th March 2015) - Chen, Guoxing; Silva, Tiago; Georgieva, Violeta; Godfroid, Thomas; Britun, Nikolay; Snyders, Rony; Delplancke-Ogletree, Marie Paule
Abstract: In this research, conversion of carbon dioxide and water vapor into value-added chemicals has been investigated in a pulsed surfacewave sustained microwave discharge operating under different conditions. Formation of syngas (CO/H2 ) was observed. The influence of the gas mixture ratio, the specific energy input (SEI), E spec, and the feed flow rate on H2 and CO production, was studied. It is found that syngas with a ratio close to 1 can be produced when CO2 – H2 O ratio in the gas mixture is 50:50. The optimum SEI for H2 and CO formation for this gas mixture ratio is 1.6 eV/mol. Experiments carried out with Ar/H2 O showed that the presence of CO2 supports the H2 formation at low SEI. Increasing the feed flow rate, i.e. reducing the residence time, hinders the H2 yield while the CO yield initially decreases and reaches a stable level. The highest energy conversion efficiency is calculated to be at low SEI and low flow rate. Optical emission spectroscopy measurements show that comparatively high dissociation rates correspond to low gas temperatures. Highlights: Simultaneous dissociation of CO2 and H2 O by microwave plasma. Conversion and energy efficiency dependence on flow rate and specific energy input. Discharge composition characterization by optical emission spectroscopy. Gas temperature is estimated based on the analysis of OH rotational bands.